2014
DOI: 10.1136/ejhpharm-2013-000403
|View full text |Cite
|
Sign up to set email alerts
|

The rate and nature of medication errors among elderly upon admission to hospital after implementation of clinical pharmacist-led medication reconciliation

Abstract: Objectives To determine the frequency and nature of erroneous transfer of medication information (medication errors) upon admission to hospital and to study the effect of medication reconciliation. Methods Included patients were 65 years of age or older, were living in nursing homes or in their own home with care provided by the community nursing system and had been admitted to hospital. The patients’ medication lists from the community were compared with the hospital medication lists upon admission in order … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The value of the pharmacist in medicines reconciliation was also shown in a Swedish medical ward though the researchers suggested more work is needed. 20 …”
Section: Discussionmentioning
confidence: 99%
“…The value of the pharmacist in medicines reconciliation was also shown in a Swedish medical ward though the researchers suggested more work is needed. 20 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we presume that patients often did not report all drugs and recreational products, even on request. Studies on medication reconciliation showed that the way questions are phrased strongly influences the number of reported drugs . In addition, we found documented diseases requiring treatment without mention of a corresponding drug.…”
Section: Discussionmentioning
confidence: 69%
“…Studies on medication reconciliation showed that the way questions are phrased strongly influences the number of reported drugs. [55][56][57][58] In addition, we found documented diseases requiring treatment without mention of a corresponding drug. Another limiting factor was the poor quality of information on potential ADRs on male fertility.…”
Section: Limitationsmentioning
confidence: 99%
“…The use of computerized physician order entry reduced medication prescription errors to 3.4 % of orders in comparison to paper-based orders where the error rate was about 27 % in one study [17]. The study site is also covered by pharmaceutical care services, where clinical pharmacists review and follow up all patients medication from admission till discharge, which may have significantly impacted the incidence of medication errors [18]. The availability of pharmacist support for more than 15 hours per day has been associated with a higher interception of near misses and prescribing errors in one study [19].…”
Section: Discussionmentioning
confidence: 99%